Development and experiment of the mechanism for oolong tea stirring motion based on the manual stirring characteristics analysis - Chen, Jianneng; Yao, Kun; Zhou, Binsong; Zhao, Xiong; Bian, Xianbing; Zhu, Zheng; Jia, Jiangming (International Journal of Agricultural and Biological Engineering, 2023)
In this study, the motion characteristics of manual stirring were analyzed to achieve the goal of realizing a high-quality mechanized imitation of manual stirring for oolong tea. A test bench for collecting the motion characteristics of manual stirring was designed, and the standard manual stirring motion characteristic curve was obtained. According to the requirements of the stirring motion characteristics, a variable-speed and variable-amplitude stirring mechanism was proposed, the kinematics model and reverse design model of the stirring mechanism were established, auxiliary analysis and design software were written, and the non-circular gear pitch curve and cam profile curve were obtained. A three-dimensional model of the stirring machine was established, a virtual prototype of the stirring machine was built, and the simulation experiment was completed by using the ADAMS software. A prototype of the stirring machine was developed, and the stirring experiment was conducted on the prototype. The maximum deviation of the pitch angle is 2.8772°, and the maximum deviation of the roll angle is 1.5948° according to the analysis and comparison of the actual curve data and the theoretical data curve. The experimental results showed that the simulation angle curve and the actual angle curve were consistent with the theoretical standard manual stirring motion characteristic curve, which verified the correctness of the design and modeling of the stirring mechanism. The tea was mechanically stirred by the stirring mechanism to achieve the desired stirring effect, which verified the feasibility of the stirring machine. Keywords: oolong tea, stirring motion, mechanism, manual stirring, development, experiment DOI: 10.25165/j.ijabe.20231605.7524 Citation: Chen J N, Yao K, Zhou B S, Zhao X, Bian X B, Zhu Z, et al. Development and experiment of the mechanism for oolong tea stirring motion based on analyzed manual stirring characteristics. Int J Agric & Biol Eng, 2023; 16(5): 260-269.